Vemurafenib: an unusual UVA‐induced photosensitivity - P. Gélot; H. Dutartre; Amir Khammari; Aurélie Boisrobert; Caroline Schmitt; Jean‐Charles Deybach; Jean‐Michel Nguyen; Sophie Seité; Brigitte Dréno (2013)
Vemurafenib is a new-targeted therapy approved for the treatment of patients with V600E BRAF-mutant metastatic melanoma. Among the cutaneous adverse events reported, the photosensitivity is frequently experienced. We aimed to characterize more deeply the mechanism leading to this photosensitivity as well as the corresponding UV spectrum. Phototests showed that the phototoxicity was UVA-dependent since from normal value prior to vemurafenib treatment, the UVA-minimal erythema dose decreased in 17 of 18 patients (94.4%) while the minimal erythema dose remained unchanged. Furthermore, a vemurafenib-induced erythema appeared quickly during the UVA exposure contrarily to what is observed with a conventional drug-induced phototoxicity showing an erythema 12-24 h after the phototesting. Vitamin PP concentration decreased, and porphyrin level significantly increased after 2 months of vemurafenib. Our study confirms the high risk of vemurafenib-induced photosensitivity and indicates that it is possibly vitamin PP- and porphyrin dependent.